Predictors of in-hospital mortality AND death RISK STRATIFICATION among COVID-19 PATIENTS aged ≥ 80 YEARs OLD. (July 2021) - Covino, Marcello; De Matteis, Giuseppe; Polla, Davide Antonio Della; Santoro, Michele; Burzo, Maria Livia; Torelli, Enrico; Simeoni, Benedetta; Russo, Andrea; Sandroni, Claudio; Gasbarrini, Antonio; Franceschi, Francesco
Highlights: Older patients are facing a more severe COVID-19 due to age-related vulnerability Reduced PaO2 /FiO2 and consolidations at chest x-ray were predictors of mortality Age≥85 yo, dementia and impairment in ADL were predictors of in-hospital death Severity scores had good ability in death risk stratification in older people Abstract: Introduction: : To date, mainly due to age-related vulnerability and to coexisting comorbidities, older patients often face a more severe COVID-19. This study aimed to identify at Emergency Department (ED) admission the predictors of in-hospital mortality and suitable scores for death risk stratification among COVID-19 patients ≥ 80 years old. Methods: : Single-centre prospective study conducted in the ED of an university hospital, referral center for COVID-19 in central Italy. We included 239 consecutive patients ≥ 80 years old with laboratory-confirmed COVID-19. The primary study endpoint was all-cause in-hospital mortality. Multivariable Cox regression analysis was performed on significant variables at univariate analysis to identify independent risk factor for death. Overall performance in predicting mortality of WHO severity scale, APACHE II score, NEWS score, and CURB-65 was calculated. Results: : Median age was 85 [82-89] and 112 were males (46.9%). Globally, 77 patients (32.2%) deceased. The presence of consolidations at chest x-ray and the hypoxemic respiratory failure were significant predictors of poor prognosis. Moreover, age ≥ 85 years, dependency in activities of daily living (ADL), and dementia were risk factors for death, even after adjusting for clinical covariates and disease severity. All the evaluated scores showed a fairly good predictive value in identifying patients who could experience a worse outcome. Conclusions: : Among patients ≥ 80 years old hospitalized with COVID-19, not only a worse clinical and radiological presentation of the disease, but also the increasing age, dementia, and impairment in ADL were strong risk factors for in-hospital death, regardless of disease severity.